2004
DOI: 10.1128/jcm.42.3.1058-1063.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli Virulence Factors Are Found To Be Associated with Infantile Diarrhea in Brazil

Abstract: We have previously shown that enteroaggregative Escherichia coli (EAEC) is an important pathogen among Brazilian infants. Most EAEC strains harbor a plasmid (pAA) from which a DNA fragment has been used as a probe (EAEC probe). To better understand the characteristics of EAEC in Brazil, 109 strains carrying and lacking the EAEC probe sequence were tested for the presence of pAA plasmid-borne and chromosomal factors. Common virulence factors of probe-positive and probe-negative isolates included the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 33 publications
9
47
0
3
Order By: Relevance
“…ETEC and EAEC have been frequently detected in children with diarrhea in studies conducted in Brazil and in other countries (Gomes et al 1991, Nataro & Kaper 1998, Scaletsky et al 2002, Zamboni et al 2004, Regua-Mangia et al 2004, which is in agreement with the results reported in this study. EAEC is emerging as an enteric pathogen of great concern, responsible for acute and persistent diarrhea (≥ 14 days) and may cause malnutrition and growth defects in children.…”
Section: Discussionsupporting
confidence: 83%
“…ETEC and EAEC have been frequently detected in children with diarrhea in studies conducted in Brazil and in other countries (Gomes et al 1991, Nataro & Kaper 1998, Scaletsky et al 2002, Zamboni et al 2004, Regua-Mangia et al 2004, which is in agreement with the results reported in this study. EAEC is emerging as an enteric pathogen of great concern, responsible for acute and persistent diarrhea (≥ 14 days) and may cause malnutrition and growth defects in children.…”
Section: Discussionsupporting
confidence: 83%
“…Besides, pCVD432 and aggR, the most frequent plasmid-borne genes detected among the EAEC isolates were aap, irp2 and shf. These findings are in agreement with those of a previous study in Kolkata, India [10] and elsewhere [4,23]. The aap gene is under the control of aggR.…”
Section: Discussionsupporting
confidence: 83%
“…Several workers reported relatively similar results. 15,45 Recently, Harrington and others 46 suggested the term "typical EAEC" to refer to strains expressing the aggR regulon. Results of this study show an abundance of typical rather than atypical EAEC among diarrheic Libyan children, as reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%